Virtual teaching assistants: A survey of a novel teaching technology. Issue 2 (August 2022) - Audras, Diane; Zhao, Alex; Isgar, Chuck; Tang, Yucheng
This study centers around virtual teaching assistants ("VTA") and the potential application of VTAs to reduce the burden on teachers across secondary schools in China exacerbated by the Double Reduction Policy. It seeks to understand how VTAs could be implemented in the classroom while ensuring student and teacher well-being, success, and happiness. Through interviews with fourteen different experts spanning industry, academia, and education, combined with extensive review of the existing literature and ecosystem of VTAs, research shows that VTAs are potentially a major aid in the context of exam review, after school tutoring, automated grading, and student performance reporting. However, they need to be created carefully with an attentive eye towards student support to ensure that the learning experience is not diminished. It must be clearly communicated to all stakeholders that the goal of a VTA is not to replace teachers, but rather to support them such that they can spend more time with students and less time on mundane tasks.